The quantitative and qualitative allocation of ministerial portfolios to European radical right parties - Tan, Tian (Frontiers in Political Science, 2025)
This paper examines the ministerial portfolio allocation to European Radical Right Parties (RRPs) in coalition governments, focusing on both quantitative and qualitative aspects. Ministerial portfolio allocation, essential for policy implementation and government stability, typically follows the proportionality principle, aligning ministerial portfolios with seat share. Meanwhile, traditional mainstream parties often secure ministerial portfolios that match their electoral programs. This study investigates whether RRPs—long regarded as “pariah parties”, despite their increasing participation in coalition governments since the early twenty-first century, often entering as weak junior partners and maintaining a hostile stance toward liberal democracy—follow these allocation patterns. Our analysis shows that while RRPs exhibit a proportional seat-to-portfolio share relationship, their allocations are more strongly influenced by bargaining power. Moreover, RRPs often fail to obtain ministerial portfolios aligned with their electoral priorities. Thus, while RRPs appear normalized in terms of quantitative allocation, they continue to face significant qualitative challenges.